Aneurysmal subarachnoid hemorrhage lead to systemic upregulation of IL-23/IL-17 inflammatory axis. (September 2017) - Chaudhry, Shafqat Rasul; Güresir, Erdem; Vatter, Hartmut; Kinfe, Thomas M.; Dietrich, Dirk; Lamprecht, Alf; Muhammad, Sajjad
Highlights: Serum IL-23 and IL-17 were elevated in aSAH as compared to controls and may play a role in the pathophysiology of aSAH. Elevated serum IL-23 and IL-17 levels showed differential associations with different post aSAH complications. Serum IL-23 and IL-17 levels did not correlate with clinical outcome. Abstract: IL-23 and IL-17 are pro-inflammatory cytokines. IL-23 is secreted by activated macrophages and dendritic cells, while IL-17 by Th17 cells. Serum IL-23 and IL-17 are known to be elevated in numerous inflammatory diseases including neurodegenerative diseases. The role of serum IL-23 and IL-17 in aneurysmal subarachnoid hemorrhage (aSAH) has still not been investigated. The present work investigates the serum IL-23 and IL-17 levels and their association with post hemorrhagic complications and clinical outcome in patients with aSAH. Methods: In this study, 80 patients with aSAH (Hunt and Hess grade I-V) were prospectively recruited. We enrolled 24 control patients with lumbar spinal stenosis. Peripheral venous blood was withdrawn from controls and from aSAH patients at day 1 and day 7, allowed to clot and centrifuged to obtain serum. Enzyme linked immunoassay kits were employed to quantify the serum levels of IL-23 and IL-17 by applying 50 µL of serum samples. Post hemorrhagic complications and clinical outcome were documented prospectively from patient's hospital record. Results: Serum IL-23 and IL-17 levels were significantly elevated in aSAH patients at day 1 and day 7 (n = 80) as compared to control patients (n = 24). Further analysis after dichotomy of patients who suffered from post hemorrhagic complications including cerebral vasospasm, chronic hydrocephalus, seizures, cerebral ischemia, delayed neurological deficits showed differential correlations with different post hemorrhagic complications (Table 1). Serum IL-23 and IL-17 levels did not correlate with clinical outcome. Conclusion: Serum IL-23 and IL-17 levels were elevated in patients with aSAH showing upregulation of IL-23/IL-17 inflammatory axis after aSAH. Serum IL-23 and IL-17 showed differential correlations with post hemorrhagic complications and no correlation with clinical outcome.